The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1371/journal.pone.0143135
|View full text |Cite|
|
Sign up to set email alerts
|

Protective Effects of Dietary Supplementation with a Combination of Nutrients in a Transgenic Mouse Model of Alzheimer’s Disease

Abstract: ObjectiveThis study investigated the effects of intervention with a combination of nutrients in the amyloid precursor protein-presenilin (APP-PSN) C57BL/6J double transgenic mouse model of Alzheimer’s disease (AD).MethodsA total of 72 2-month-old APP-PSN mice were randomly assigned to three groups. The model group (MG) was fed regular, unsupplemented chow, while the low- and high-dose treatment groups (LG and HG, respectively) were given a combination of nutrients that included phosphatidylserine, blueberry ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 45 publications
(42 reference statements)
0
3
0
Order By: Relevance
“…The former are markers of neuronal and glial function whereas the latter are markers of pathological changes. As stated previously, biomarkers Blueberry supplementation has been shown in some prior studies to benefit cognitive aging and preclinical studies have reported that blueberry bioactives may provide anti-oxidant benefits, enhance microglial clearance of Aβ, inhibit aggregation of Aβ42, or suppress microglial activation and provide protection against Aβ-induced neurotoxicity (reviewed in [7][8][9][10][11][12][13][14][15][16][17]. Blueberry supplementation has also been reported to improve cognition in pilot studies of MCI (16,17).…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…The former are markers of neuronal and glial function whereas the latter are markers of pathological changes. As stated previously, biomarkers Blueberry supplementation has been shown in some prior studies to benefit cognitive aging and preclinical studies have reported that blueberry bioactives may provide anti-oxidant benefits, enhance microglial clearance of Aβ, inhibit aggregation of Aβ42, or suppress microglial activation and provide protection against Aβ-induced neurotoxicity (reviewed in [7][8][9][10][11][12][13][14][15][16][17]. Blueberry supplementation has also been reported to improve cognition in pilot studies of MCI (16,17).…”
Section: Discussionmentioning
confidence: 89%
“…Practical, well-tolerated, and non-invasive lifestyle interventions are highly desirable for AD prevention in at-risk middle-aged and older adults (3)(4)(5)(6)(7)(8)(9). Evidence from epidemiological, pre-clinical and pilot clinical studies suggests that regular consumption of blueberries may protect against cognitive decline or dementia (7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17). Blueberries contain high levels of micronutrients and antioxidants (such as anthrocyanins) which in preclinical studies have been found to impact many pathways involved in cognitive function or dementia risk -such as reduced oxidative stress, improved inflammatory response, reversed age-related decrements in cognition, increased cerebral blood flow, enhanced microglial clearance of Aβ, inhibited aggregation of Aβ42, suppressed microglial activation and protection against Aβ-induced neurotoxicity (reviewed in 7,[12][13][14][15][16][17].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Meanwhile, a combination of nutrients like phosphatidylserine, blueberry extracts, docosahexaenoic acid (DHA), and eicosapentaenoic acid (EPA) are categorized under omega-3 fatty acids was also found to increase the level of acetylcholine by reducing the total cholinesterase (TChE) level in the brain of the AD transgenic mouse model [51]. Altogether, this supplementation improves memory and cognitive function and can be recommended as a complementary therapy for cognitive decline.…”
Section: Nutraceuticals Effects On the Inhibition Of Reuptake Enzymesmentioning
confidence: 99%
“…Generally, it is acknowledged that MI is closely related to oxygen radicals, vascular endothelial injury, and myocardial cell apoptosis [ 4 ]. Moreover, cardiomyocyte apoptosis and necrosis triggered by MI result in the loss of cardiomyocytes, which may further lead to a significant decrease in heart pumping and congestive heart failure [ 5 ]. Previous research has shown that timely reperfusion treatment for acute myocardial infarction (AMI), by shrinking the myocardial necrosis zone, may cause reperfusion injury [ 6 – 11 ].…”
Section: Introductionmentioning
confidence: 99%